Environmental Regulation and Corporate Innovation Behavior Based on the “Double Carbon” Strategy – Empirical Analysis Based on A-Share Listed Companies of Heavy Pollution Industries on the Shanghai and Shenzhen Stock Exchanges - Ying, Nie; Yao, Li; Jihong, Xin; Daqing, Wang (Frontiers in Ecology and Evolution, 2022)
Environmental regulations have been intensified across the country under the pressure of the national “double carbon” strategy, the constraints of energy-saving and emission-reduction targets by enterprises, and public opinion. The tightening of environmental regulations is bound to impact the innovation behavior of heavily polluting enterprises; however, it remains uncertain whether the impact is positive or negative. Using a differences-in-differences approach of data from listed companies in China’s heavily-polluting industries between 2010 and 2016, this paper examines the changes in their innovation behavior under the tightening environmental regulations after the “smog explosion” event as a “quasi-natural experiment” at the end of 2011. The study found that the “smog event” had a significant net negative effect on the innovation behavior of heavily polluting firms, with a significant decrease in their innovation inputs. The quantile regression results show that the R&D intensity of enterprises is related to the haze treatment effect in a U-shaped curve. Further research found that the decline in innovation investment was more significant for state-owned heavily-polluting firms compared to private heavy polluting firms. Robustness tests indicate that the empirical results of this paper are somewhat robust. This paper aims to identify the contradictory roots of the “Porter hypothesis” debate by analyzing the differences in innovation behavior of enterprises with different R&D intensity and different property rights.